Classical Limit, Quantum Border and Energy - Andres Mauricio Kowalski; Angelo Plastino; Gaspar Gonzalez (Physics, 2023)
We analyze the (dynamical) classic limit of a special semiclassical system. We describe the interaction of a quantum system with a classical one. This limit has been well studied before as a function of a constant of motion linked to the Heisenberg principle. In this paper, we investigate the existence of the mentioned limit, but with reference to the total energy of the system. Additionally, we find an attractive result regarding the border of the transition.